MODERNIZATION OF A NATIONAL POWER SYSTEM AS GEOPOLITICAL FACTOR OF A SUSTAINABLE DEVELOPMENT - N. I. Komkov; M. N. Dudin; N. V. Lyasnikov (Модернизация, инновация, развитие)
The main features and approaches to implementation of scientific and technological modernization of a national power system are considered. The interrelation between a sustainable development of economy, fuel and energy complex, power efficiency and energy security, as the major factors defining geopolitical positions of the state is defined. It is revealed that for ensuring modernization of a national power system it is necessary to be guided not so much by breakthrough scenarios of full reorganization of fuel and energy complex, how many by the scenarios based on systematic system transformation of all national economy. These scenarios are a basis for successful transition from traditional industrial development to innovative post-industrial type both at level to national economy, and at the level of separate branches.